Divinity, disease, and death : an analysis of theological concepts of suffering in the bible and their reflection in selected medieval Latin and Middle High German texts in the High Middle ages - Byrne, Judith J. (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2006)
This thesis focuses on religious ideas associated with suffering, caused by disease or injury, in the High Middle Ages. The condition of death, although frequently excluded from other studies, is included here as its significance is too important to overlook. According to the Bible, God imposes suffering for various reasons, including as a punishment (retributive in nature, penalising specific behaviour), a chastisement (disciplinary in nature, aimed at repentance), a test of faith, or a means of manifesting His power. This study employs a comparative and interdisciplinary approach, exploring religious concepts of suffering through the Old Testament, the New Testament, the writings of certain early Christian figures, Greek and Latin Fathers of the Church, and medieval commentators, including Tertullian, Augustine, Gregory the Great, Ambrose of Milan, Basil of Caesarea and Gregory of Nazianzus, Alcuin, Hrabanus Maurus, Johannes Andreae and Nicholas de Tudeschis.
Keywords: Germanic Studies, Ph.D.; Ph.D. Trinity College Dublin